CREATION OF QUESTIONNAIRE KEYWORDS WITH THE CISE METHOD FOR KMS USER SATISFACTION EVALUATION - Teja Endra Eng Tju (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2022)
This study aims to obtain user satisfaction factors for a knowledge management system so that a questionnaire can be made for evaluation or measurement. The SECI method is used with the CISE sequence which consists of four knowledge creation steps, namely C-combination, I-nternalization, S-socialization, and ending E-externalization. The stage begins with literature studies and then modifications are made with the selection, addition, and incorporation of existing models. From understanding and analyzing several models, discussions or brainstorming with colleagues were then carried out so that a final model was obtained to compile a list of keywords and statements as a questionnaire based on indicators related to knowledge management and the satisfaction of knowledge management system users. The results obtained there are eight user satisfaction factors divided into technical aspects (knowledge quality, knowledge sharing, system quality, service quality) and social aspects (management support, system use, perceived usefulness, user attribute). Five attributes were obtained from each of these factors as keywords resulting in 40 questionnaire statements. It can be concluded that the factors of user satisfaction knowledge management system can be built from the satisfaction of information system users in general by adding distinctive factors including the creation, transfer, and documentation of knowledge.